Efficient and stable perovskite solar cells through e-beam preparation of cerium doped TiO2 electron transport layer, ultraviolet conversion layer CsPbBr3 and the encapsulation layer Al2O3. (1st March 2020) - Jin, Junjie; Li, Hao; Bi, Wenbo; Chen, Cong; Zhang, Boxue; Xu, Lin; Dong, Biao; Song, Hongwei; Dai, Qilin
Graphical abstract: Highlights: Using the e-beam method to fabricate the Ce doped TiO2 as the electron transport layer. Introduce the CsPbBr3 quantum dots as the ultraviolet to visible conversion layer to improve the light stability. Using the e-beam method to prepare the Al2 O3 encapsulation layer to improve the moisture stability. The modified device can maintain 90% of initial efficiency after aging 4000 h in the ambient air. Abstract: The electron transport layer (ETL) as an important part for high performing perovskite solar cells (PSCs), can transport photogenerated electrons while block holes. TiO2, as the usual ETL in the PSCs, may cause charge recombination in the device due to its poor electron conductivity. In order to improve the conductivity, we doped the Ce ions into TiO2 and used the e-beam method to fabricate the ETL layer. The doping of Ce could facilitate the charge transport and reduce the charge recombination, resulting in the increased power conversion efficiency (PCE) from 17.98% to 19.34%. And more, we also enhanced the stability of PSCs through the introduction of CsPbBr3 quantum dots (QDs) and Al2 O3 . As the ultraviolet (UV) to visible conversion layer, CsPbBr3 QDs were coated on the incident light side of the device to enhance the light stability of PSCs, while, as an encapsulation layer, the Al2 O3 was put on the back side of the device to enhance the long-term stability of PSCs. As a result, the modified device can maintain 90% of initial efficiency after aging 4000 h in the ambient air.